2009
DOI: 10.1124/jpet.108.149815
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Transporters and Enzymes by the Vitamin D Receptor Ligands, 1α,25-Dihydroxyvitamin D3and Vitamin D Analogs, in the Caco-2 Cell Monolayer

Abstract: The effects of 1␣,25-dihydroxyvitamin D 3 [1,25(OH) 2 D 3 ] on gene expression and function were studied in Caco-2 cells. Microarray analyses, real-time quantitative polymerase chain reactions, and Western blotting were used to determine the mRNA and protein expression of transporters and enzymes after 1,25(OH) 2 D 3 or vehicle (0.1% ethanol) treatment for 1, 3, 6, and 10 days. The mRNA and protein expressions of the apical sodium-dependent bile acid transporter, oligopeptide transporter 1, multidrug resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
118
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 89 publications
(124 citation statements)
references
References 40 publications
5
118
1
Order By: Relevance
“…Although all three drugs are primarily metabolized by CYP3A (Lampen et al, 1998;Iwasaki, 2007;Staatz et al, 2010), they are also substrates of the drug efflux pump P-glycoprotein (P-gp), which limits oral bioavailability by pumping absorbed drug molecules back to the intestinal lumen (Lo and Burckart, 1999). Similar to CYP3A4, P-gp is induced by vitamin D, but at the vitamin D concentration investigated (1,25(OH) 2 vitamin D 3 100 nM) the level of P-gp induction is much lower than that of CYP3A4 (Fan et al, 2009). If the relative influence of CYP3A4 and P-gp on the overall bioavailability varies among cyclosporine, sirolimus, and tacrolimus, this could affect their sensitivity to vitamin D-associated enzyme induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although all three drugs are primarily metabolized by CYP3A (Lampen et al, 1998;Iwasaki, 2007;Staatz et al, 2010), they are also substrates of the drug efflux pump P-glycoprotein (P-gp), which limits oral bioavailability by pumping absorbed drug molecules back to the intestinal lumen (Lo and Burckart, 1999). Similar to CYP3A4, P-gp is induced by vitamin D, but at the vitamin D concentration investigated (1,25(OH) 2 vitamin D 3 100 nM) the level of P-gp induction is much lower than that of CYP3A4 (Fan et al, 2009). If the relative influence of CYP3A4 and P-gp on the overall bioavailability varies among cyclosporine, sirolimus, and tacrolimus, this could affect their sensitivity to vitamin D-associated enzyme induction.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have indicated that vitamin D may induce the expression of CYP3A4 by a vitamin D receptor-mediated increase in gene transcription (Schmiedlin-Ren et al, 1997;Fan et al, 2009), and this activity would result in increased metabolism of CYP3A4 drug substrates. Indeed, these molecular findings suggest a potential influence of vitamin D on the turnover of many drugs, but the relevance for drug exposure in patients has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 1,25(OH) 2 D 3 regulates many other genes related to proliferation, including MYC, FOS and JUN (Pálmer et al 2001, 2003, Meyer et al 2012. The c-MYC oncogene is deregulated and over-expressed in most cancers, and its down-regulation by 1,25(OH) 2 Fan et al (2009) in vitro model developed to evaluate the cross talk between tumour-associated macrophages and CRC cells, 1,25(OH) 2 D 3 restores the sensitivity of CRC cells to TRAIL-induced apoptosis by interfering with the release of IL1b by macrophages (Kaler et al 2010).…”
Section: 25(oh) 2 D 3 Is a Pleiotropic Hormonementioning
confidence: 99%
“…VDR-responsive drug-metabolizing enzymes include the cytochrome P-450s [human CYP3A4, CYP2B6, and CYP2C9 (17,50), and rodent Cyp3a1, Cyp3a9, and Cyp24a1 (12,14)] and sulfotransferase-2A1 (SULT2A1) (20). VDRresponsive transporters include the rat apical sodium-dependent bile acid transporter (Asbt) (10), human organic aniontransporting polypeptide (OATP1A2) (21), multidrug resistance protein-1 or P-glycoprotein (MDR1/P-gp) (44), and the human and rodent multidrug resistance-associated proteins (MRP2/Mrp2, Mrp3, MRP4/Mrp4) both in vitro and in vivo (14,22). Our laboratory has shown that VDR transactivates P-gp in brain microvessel endothelia (18) in vitro and P-gp in murine kidney and brain but not ileum and liver in vivo, leading to hastened efflux of digoxin in the brain and kidney (11).…”
mentioning
confidence: 99%